Does Adopting Western Low-density Lipoprotein Cholesterol Targets Expose Indians to a Higher Risk of Cardiovascular Events? Expert Opinion From the Lipid Association of India - Puri, Raman; Mehta, Vimal; Bansal, Manish; Duell, P Barton; Iyengar, S S; Shetty, Sadanand; Graham, Ian; Mohan, J C; Kaul, Upendra; Rao, Dayasagar; Agarwala, Rajeev; Wander, Gurpreet Singh; et al. (Journal of the Association of Physicians of India, 2024)
Adverse cardiovascular (CV) events have declined in Western countries due at least in part to aggressive risk factor control, including dyslipidemia management. The American and European (Western) dyslipidemia treatment guidelines have contributed significantly to the reduction in atherosclerotic cardiovascular disease (ASCVD) incidence in the respective populations. However, their direct extrapolation to Indian patients does not seem appropriate for the reasons described below. In the US, mean low-density lipoprotein cholesterol (LDL-C) levels have markedly declined over the last 2 decades, correlating with a proportional reduction in CV events. Conversely, poor risk factor control and dyslipidemia management have led to increased CV and coronary artery disease (CAD) mortality rates in India. The population-attributable risk of dyslipidemia is about 50% for myocardial infarction, signifying its major role in CV events. In addition, the pattern of dyslipidemia in Indians differs considerably from that in Western populations, requiring unique strategies for lipid management in Indians and modified treatment targets. The Lipid Association of India (LAI) recognized the need for tailored LDL-C targets for Indians and recommended lower targets compared to Western guidelines. For individuals with established ASCVD or diabetes with additional risk factors, an LDL-C target of <50 mg/dL was recommended, with an optional target of ≤30 mg/dL for individuals at extremely high risk. There are several reasons that necessitate these lower targets. In Indian subjects, CAD develops 10 years earlier than in Western populations and is more malignant. Additionally, Indians experience higher CAD mortality despite having lower basal LDL-C levels, requiring greater LDL-C reduction to achieve a comparable CV event reduction. The Indian Council for Medical Research-India Diabetes study described a high prevalence of dyslipidemia among Indians, characterized by relatively lower LDL-C levels, higher triglyceride levels, and lower high-density lipoprotein cholesterol (HDL-C) levels compared to Western populations. About 30% of Indians have hypertriglyceridemia, aggravating ASCVD risk and complicating dyslipidemia management. The levels of atherogenic triglyceride-rich lipoproteins, including remnant lipoproteins, are increased in hypertriglyceridemia and are predictive of CV events. Hypertriglyceridemia is also associated with higher levels of small, dense LDL particles, which are more atherogenic, and higher levels of apolipoprotein B (Apo B), reflecting a higher burden of circulating atherogenic lipoprotein particles. A high prevalence of low HDL-C, which is often dysfunctional, and elevated lipoprotein(a) [Lp(a)] levels further contribute to the heightened atherogenicity and premature CAD in Indians. Considering the unique characteristics of atherogenic dyslipidemia in Indians, lower LDL-C, non-HDL-C, and Apo B goals compared to Western guidelines are required for effective control of ASCVD risk in Indians. South Asian ancestry is identified as a risk enhancer in the American lipid management guidelines, highlighting the elevated ASCVD risk of Indian and other South Asian individuals, suggesting a need for more aggressive LDL-C lowering in such individuals. Hence, the LDL-C goals recommended by the Western guidelines may be excessively high for Indians and could result in significant residual ASCVD risk attributable to inadequate LDL-C lowering. Further, the results of Mendelian randomization studies have shown that lowering LDL-C by 5-10 mg/dL reduces CV risk by 8-18%. The lower LDL-C targets proposed by LAI can yield these incremental benefits. In conclusion, Western LDL-C targets may not be suitable for Indian subjects, given the earlier presentation of ASCVD at lower LDL-C levels. They may result in greater CV events that could otherwise be prevented with lower LDL-C targets. The atherogenic dyslipidemia in Indian individuals necessitates more aggressive LDL-C and non-HDL-C lowering, as recommended by the LAI, in order to stem the epidemic of ASCVD in India.